Cardiovascular morbidity and mortality related to non-alcoholic fatty liver disease: a systematic review and meta-analysis of prospective studies. (14th October 2021) - Bisaccia, G; Ricci, F; Melchiorre, E; Tana, C; Renda, G; Khanji, M Y; Fedorowski, A; De Caterina, R; Gallina, S
Abstract: Background: Whether non-alcoholic fatty liver disease (NAFLD) is a risk factor for cardiovascular (CV) events is still debated. Currently available evidence derives from non-homogeneous studies yielding conflicting results. Purpose: We set out to assess the relationship between NAFLD and CV morbidity and mortality by pooling results of previous studies. Methods: We performed a systematic review and meta-analysis of prospective observational studies published from 1966 through 2021 reporting summary-level outcome data in subjects with and without NAFLD. Adjusted risk ratios (RRs) and 95% confidence intervals (CIs) for all-cause mortality, CV mortality, myocardial infarction (MI), stroke, major adverse cerebrocardiovascular events (MACCE) and atrial fibrillation (AF) were pooled through inverse variance random-effect meta-analysis to compute the summary effect size. We performed post-hoc subgroup analysis stratified by geographical region and univariate mixed-effect model meta-regression analysis to address statistical heterogeneity. Results: We identified a total of 29 studies pooling an overall population of 5, 626, 573 middle-aged individuals (mean age 56±8; male sex 53%; NAFLD 5.8%, n=326, 389). Mean follow-up was 10±6 years. Compared with control population, presence of NAFLD was associated with similar risk of all-cause death (RR 1.17; 95% CI 0.89–1.52) and CV death (RR 0.84; 95% CI 0.64–1.10). When analysed by geographic location, pooled estimates of RR (95% CI) for all-cause death were 1.57 (1.00–2.48) for Western countries, and 0.81 (0.52–1.1.26) for Eastern countries (test for subgroup difference, P=0.04). Meta-regression analysis showed a stronger relationship between NAFLD and all-cause mortality proportional to increasing body mass index (P=0.048). NAFLD was associated with increased risk of myocardial infarction (RR 1.35; 95% CI 1.09–1.68), stroke (RR 1.20; 95% CI 1.06–1.35), MACCE (RR 2.09; 95% CI 1.57–2.78) and atrial fibrillation (RR 1.37; 95% CI 1.05–1.78). Conclusion: NAFLD portends excess all-cause mortality but only in Western countries. CV mortality was similar in NAFLD and non-NAFLD groups. NAFLD is associated with increased risk of incident MI, stroke, MACCE and AF. FUNDunding Acknowledgement: Type of funding sources: None.